1977
DOI: 10.1093/jaoac/60.3.509
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Urethane in Wines by Gas-Liquid Chromatography and Its Confirmation by Mass Spectrometry

Abstract: A gas-liquid chromatographic (GLC)-mass spectral (MS) method for the determination and confirmation of urethane in wines has been developed. Analyses of domestic and imported wines indicated urethane to be present at levels ranging from 1 to 20 μg/L. Recoveries of urethane from wines fortified at 10 ppb (μg/L) ranged from 50 to 100% with an average value of 71%. GLC-MS was used to confirm the identity of urethane in wine extracts in which GLC indicated the presence of urethane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…ETHYL CARBAMATE (EC), a well-known carcinogen, has been detected at low concentrations (in the µg/L range) in fermented foods and beverages (Walker et al, 1974;Joe et al, 1976;Canas et al, 1989, Dennis et al, 1989. Lofroth and sGejvall (1971) reported that EC in alcoholic beverages was derived from the reaction between ethanol and diethylpyrocarbonate (DEPC), an antimicrobial agent.…”
Section: Introductionmentioning
confidence: 99%
“…ETHYL CARBAMATE (EC), a well-known carcinogen, has been detected at low concentrations (in the µg/L range) in fermented foods and beverages (Walker et al, 1974;Joe et al, 1976;Canas et al, 1989, Dennis et al, 1989. Lofroth and sGejvall (1971) reported that EC in alcoholic beverages was derived from the reaction between ethanol and diethylpyrocarbonate (DEPC), an antimicrobial agent.…”
Section: Introductionmentioning
confidence: 99%
“…Ethyl carbamate has previously been identified in wines (Walker et al, 1974;Joe et al, 1976) and other fermented products such as beer, ale, sake, olives, soy sauce, and yogurt (Ough, 1976a,b). Various methods have been published for the determination of ethyl carbamate.…”
mentioning
confidence: 98%
“…Shortly after, Ough (1976a) described a method sensitive to 10 Mg L~x in which residues of ethyl carbamate were identified after cleanup using a Coulson nitrogen detector. Another method (Joe et al, 1976) described the use of an alkali flame ionization detector (AFID) or flame ionization detector (FID) for the detection of urethane with confirmation of ethyl carbamate by GLC-MS. Both El (electron ionization) and Cl (chemical ionization) modes of mass spectrometry have been demonstrated (FDA, 1972;Joe et al, 1976).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, the concentration is low in wine and high in some spirits; the concentration is particularly high in some plum brandies but is low in gin and vodka. Literature methods [ 1 , 2 , 3 ] rely on sample clean-up followed by packed- column GC and detection by FID, alkali flame ionisation, electron capture, or Coulson electrolytic conductivity detector and allow measurements down to 10 μg/L. The clean-up procedure required for levels below 100 μg/L is extensive and MS confirmation is still required.…”
Section: Introductionmentioning
confidence: 99%